2021
DOI: 10.3390/ma15010187
|View full text |Cite
|
Sign up to set email alerts
|

Nondegenerate Polycrystalline Hydrogen-Doped Indium Oxide (InOx:H) Thin Films Formed by Low-Temperature Solid-Phase Crystallization for Thin Film Transistors

Abstract: We successfully demonstrated a transition from a metallic InOx film into a nondegenerate semiconductor InOx:H film. A hydrogen-doped amorphous InOx:H (a-InOx:H) film, which was deposited by sputtering in Ar, O2, and H2 gases, could be converted into a polycrystalline InOx:H (poly-InOx:H) film by low-temperature (250 °C) solid-phase crystallization (SPC). Hall mobility increased from 49.9 cm2V−1s−1 for an a-InOx:H film to 77.2 cm2V−1s−1 for a poly-InOx:H film. Furthermore, the carrier density of a poly-InOx:H f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In general, for degenerate transparent conducting oxide materials, the mobility in the grains is determined by an optical method using the Drude model, because optical mobilities are not affected by grain boundary scattering [ 32 , 33 ]. However, it is difficult to determine the optical mobility of In 2 O 3 :H films annealed at T ann ≥ 250 °C because the free electrons are significantly decreased to the order of 10 17 cm −3 and the films become non-degenerate semiconductors [ 34 , 35 ]. Therefore, we evaluated the effects of intragrain scattering by measuring the field-effect mobility of In 2 O 3 :H TFTs.…”
Section: Resultsmentioning
confidence: 99%
“…In general, for degenerate transparent conducting oxide materials, the mobility in the grains is determined by an optical method using the Drude model, because optical mobilities are not affected by grain boundary scattering [ 32 , 33 ]. However, it is difficult to determine the optical mobility of In 2 O 3 :H films annealed at T ann ≥ 250 °C because the free electrons are significantly decreased to the order of 10 17 cm −3 and the films become non-degenerate semiconductors [ 34 , 35 ]. Therefore, we evaluated the effects of intragrain scattering by measuring the field-effect mobility of In 2 O 3 :H TFTs.…”
Section: Resultsmentioning
confidence: 99%
“…For TFT applications, Magari and Kataoka et al demonstrated poly-InO x :H TFTs with field-effect mobility of 139 cm 2 Vs −1 . [30][31][32] Most of the research on SPC poly-InO x :H films has focused on film thickness of more than 100 nm for TCO applications. On the other hand, there are few papers on the study of SPC poly-InO x :H for TFT applications with a thickness of less than 50 nm.…”
Section: Introductionmentioning
confidence: 99%